2019
DOI: 10.1515/nanoph-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of epsilon-near-zero modes via resonant tunneling in layered metal-insulator double nanocavities

Abstract: The coupling between multiple nanocavities in close vicinity leads to the hybridization of their modes. Stacked metal-insulator-metal (MIM) nanocavities constitute a highly versatile and very interesting model system to study and engineer such mode coupling, as they can be realized by lithography-free fabrication methods with fine control on the optical and geometrical parameters. The resonant modes of such MIM cavities are epsilon-near-zero (ENZ) resonances, which are appealing for nonlinear photophysics and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 54 publications
(67 reference statements)
2
43
0
Order By: Relevance
“…This would translate to a faster electron−phonon coupling and thus enable even higher switching speeds of the cavity. Moreover, the MIM nanocavity can be engineered to work at a desired wavelength, from UV to mid-IR, with practically no limitation regarding the materials involved, and the free spectral range between the ENZ resonances can be easily engineered by exploiting multiple cavity geometries, without affecting the Q-factor of the resonances 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would translate to a faster electron−phonon coupling and thus enable even higher switching speeds of the cavity. Moreover, the MIM nanocavity can be engineered to work at a desired wavelength, from UV to mid-IR, with practically no limitation regarding the materials involved, and the free spectral range between the ENZ resonances can be easily engineered by exploiting multiple cavity geometries, without affecting the Q-factor of the resonances 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been found that resonances occurring in metal-insulatormetal (MIM) nanocavities can be described as effective ENZ resonances 19 . Several ENZ points, which can be excited with both TM and transverse electric (TE) polarized light, can be designed at will, and their spectral position can be easily engineered by acting on the refractive index and thickness of the embedded dielectric, while their quality(Q)-factor (λ/Δλ) can be optimized by adopting non-symmetric geometries, yielding low reflectance R at the ENZ modes 20,21 . Therefore, these systems constitute a promising and flexible alternative to natural ENZ materials.…”
mentioning
confidence: 99%
“…Thanks to their straightforward fabrication, metal/insulator/metal (MIM) cavities of various geometries have been investigated, with applications in a plethora of fields, from superabsorption to high‐resolution color printing . More recently, MIM cavity resonances have been attributed to resonant tunneling epsilon‐near‐zero (ENZ) modes that can be excited without the need of momentum matching techniques . MIM structures are highly versatile to modify the photophysical properties of fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…This has been validated by effective medium theory (EMT) studies (reported in Figure S1, Supporting Information) and by past studies. [ 70,71 ] Moreover, in contrast with the strongly light‐absorbing behavior of single metal layers, the considered nanogap structures enable transmission/reflection bands in the visible range due to their SPPs and GSPs dispersion relations. Indeed, in presence of an optical dielectric cavity, confined modes satisfy the general Fabry–Perot (FP) condition βt cav = mπ − ϕ, where β is the complex wave vector of the lightwave propagating within the cavity, m identifies the modes number generated inside the cavity, ϕ is the reflection dephase angle and t cav is the cavity thickness.…”
Section: Theoretical Frameworkmentioning
confidence: 99%